Influence of Ca²⁺ ions on the habit of KDP crystals - Javidi, S.; Enayati, R.; Iraj, M.; Aliakbari, N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
A few KDP (KH₂PO₄) and KDP:Ca²⁺ (CaCl₂) single crystals were grown based on the temperature reduction method. Investigations show that the presence of bivalent ions like Ca²⁺ could be a cause of retarded growth rate and induced crystalline lattice defects. Here the pure KDP crystals are compared with KDP:CaCl₂. Crystals of both types were also studied in aspect of other structural and optical properties.